Differentiated Instruction in Belorussian Schools - Ogurtsov, N. G. (Russian education and society, 1992)
In the search for ways to transform the schools, major hopes have been placed on the differentiation of instruction. It is expected that this will help the schools to free themselves of the necessity of teaching everyone identically, that it will strengthen the humanities orientation of education, alleviate overload, and make it possible to take the characteristics, capacities, and interests of the children into account. A system of differentiation of instruction has been in the process of adoption in the schools of Oktiabr'skii District in the city of Minsk and Slonimskii District in Grodno Region of the Belorussian SSR since 1988. Experience that has been accumulated in our country and abroad has been taken into account. Analysis has made it possible to discern the general features characterizing this form of instruction. They consist of the following. At a certain age level, generally the age of adolescence, the students are given the right to choose the direction of further instruction. Psychological and practical preparation for the instruction has been going on since primary school. The directions chosen generally involve heightened and in-depth levels of the study of cycles of school subjects. The syllabus consists of required disciplines and subjects of choice.